Analisis Implementasi Kebijakan Work From Home pada Kesejahteraan Pengemudi Transportasi Online di Indonesia - Retnowati WD Tuti (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Work from home or work from home which is currently being carried out is a follow up to President Joko Widodo's appeal at a press conference at the Presidential Palace, calling for minimization of the spread of the new type of corona virus (SARS-CoV-2) that causes Covid-19, the public is asked to work, study, and worship from home, one of which creates a system of working from home. the purpose of this study was to analyze the Implementation of Work From Home (WFH) Policy on the Welfare of Online Transportation Drivers. The method used in this study uses a library method or approach. Data collection in this research was carried out by exploring journals, books and online media. And data processing using Nvivo Plus 12. The results of the study showed that the WFH policy reduced the level of welfare of the online transportation drivers, it can be seen from the level of their needs that were still unfulfilled. Even physiological needs which should be basic needs for everyone, the need for it cannot be fulfilled because their income has decreased dramatically since the enactment of this WFH policy.